(untitled) (Journal of Fiber Bioengineering and Informatics, 2022)
Modern technologies and developments have a major impact and contributions to a massive increase in the various types of hazards to which human beings are exposed. The protection from flame, fire, heat radiation sources, etc., is a principal requisite for both civil and defense applications. Textile fabrics constructed from natural fibers have been used traditionally for ordinary protection. Hence, the focal objective of the present research work was to scrutinize the improvement in thermal resistance/insulation performance of the flame retardant cotton fabrics treated with milk casein, a biomacromolecule-based f lame retardant. Milk casein (a phosphorous-containing protein) was applied, as a green flame retardant f inishing material, on the cotton fabrics through aqueous solutions by using an industrially applicable method. In order to evaluate the thermal protective performance, single-layer casein treated cotton fabric samples were exposed to a radiant heat source at a specific radiant heat flux density (Qo) as per ISO 6942-B standard test method. The transmitted heat flux density (Qc) and heat transmission factor (TFQo) were discerned to shift towards the lower values for the casein treated cotton fabric samples as compared to untreated cotton fabric indicating the enhanced thermal protection phenomenon.